PENERAPAN KURIKULUM 2013 DALAM MATA PELAJARAN SENI BUDAYA DI SMP NEGERI 2 PAYAKUMBUH - Tetenia Saputri Yuliost; Jagar Lumbantoruan; Marzam Marzam (FBS Universitas Negeri Padang, 2017)
AbstractThis article aimed to describe the implementation of 2013 Curriculum in the Art and Culture subject at SMPN 2 Payakumbuh by investigating the teacher’s lesson plan and looking at how the learning process took place. This qualitative research were a teacher of the Art and Culture subject in class VII of SMP Negeri 2 Payakumbuh. The instrument of the research was the researcher herself, stationaries, a camera and mobile phones. The data collected were in the form of primary and secondary data. They were obtained through observation, interview, librabry study, and documentation study. Data analysis was done by classifying, displaying and describing the data and then drawing conclusions. The result of the research indicate that the Art and Culture teacher of SMP Negeri 2 Payakumbuh has worked hard to meet the target 0f 2013 curriculum and she has applied the curriculum in accordance with its guidelines. The implementation of the curriculum covers the plan and the learning process that relate to instructional materials, learning methods, learning strategies, media, and learning sources.Keywords: Implementation, 2013 Curriculum, Art and Culture